Struktur Komunitas Zooplankton di Perairan Morosari, Kecamatan Sayung, Kabupaten Demak - Noventalia, Ida; Endrawati, Hadi; Zainuri, Muhammad (977-2407769)
Morosari waters is an area with high dynamics due to rob or high tide phenomenon, which affects the community structure of zooplankton in the waters. The purpose of this study was to investigate community structure of Zooplankton around Morosari waters, Sayung District, Demak Regency. This research was conducted in the Morosari waters, Sayung District, Demak Regency. This study uses an exploratory method with data collection methods using the Sample Survey Method. Three location were stablished for this research namely Location 1 is a Morosari river estuary area, Location 2 is an area of aquaculture, Location 3 is a Pandansari river estuary area. Samples were taken 5 times, during early July to early October 2011 using a planktonnet with 45 Î¼m mesh size, sampling was done vertical sampling and horizontal sampling. The results of this study showed 41 genera for the vertical, and 45 genera for the horizontally. Average abundance obtained by the observation station was 18,40 ind/l for the vertical, and 4,80 ind/l for the horizontal. Index zooplankton diversity showed medium and obtained the average gain by the station is 2,44 for the vertical and 2,59 for the horizontally. Uniformity index indicates the type of high uniformity and obtained the average by the station is 0,87 for the vertical, and 0,80 for the horizontal. Dominance index obtained average based on the observation station is 0,12 for the vertical, and 0,31 for the horizontal.